2005
DOI: 10.1207/s15374424jccp3401_17
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Vulnerability to Depression in High-Risk Children: The Role of Insecure Attachment and Reassurance Seeking

Abstract: This study examined the relation between insecure attachment and depression in a sample of 140 children (69 boys and 71 girls; ages 6 to 14) whose parents have a history of major depressive episodes. In addition, we examined whether this relation was moderated by excessive reassurance seeking. Children completed measures assessing insecure attachment to parents, excessive reassurance seeking, and current depressive symptoms. In addition, children and their parents participated in a semistructured clinical inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 34 publications
3
76
0
2
Order By: Relevance
“…A clear model with data to support an interactional model of depression remains unavailable (Coyne, 1999), but several studies have noted links between perceptions of parental perceptions and emotional availability, theoretically related to attachment, and depression (Armsden, McCauley, Greenberg, Burke, & Mitchell, 1990;Burge et al, 1997;Cole-Detke & Kobak, 1996;. In a recently published article, Abela et al (2005) reported that severity of depressive symptoms was related to perceptions of parenting that are consistent with insecure attachment, but the relationship was moderated by the youth's excessive reassurance seeking. Attachment did not predict depression alone, but the combination of insecure attachment and excessive reassurance seeking predicted risk of more severe depression and prior history of depression in youth (Abela et al, 2005).…”
Section: Attachment-asmentioning
confidence: 99%
See 1 more Smart Citation
“…A clear model with data to support an interactional model of depression remains unavailable (Coyne, 1999), but several studies have noted links between perceptions of parental perceptions and emotional availability, theoretically related to attachment, and depression (Armsden, McCauley, Greenberg, Burke, & Mitchell, 1990;Burge et al, 1997;Cole-Detke & Kobak, 1996;. In a recently published article, Abela et al (2005) reported that severity of depressive symptoms was related to perceptions of parenting that are consistent with insecure attachment, but the relationship was moderated by the youth's excessive reassurance seeking. Attachment did not predict depression alone, but the combination of insecure attachment and excessive reassurance seeking predicted risk of more severe depression and prior history of depression in youth (Abela et al, 2005).…”
Section: Attachment-asmentioning
confidence: 99%
“…In a recently published article, Abela et al (2005) reported that severity of depressive symptoms was related to perceptions of parenting that are consistent with insecure attachment, but the relationship was moderated by the youth's excessive reassurance seeking. Attachment did not predict depression alone, but the combination of insecure attachment and excessive reassurance seeking predicted risk of more severe depression and prior history of depression in youth (Abela et al, 2005).…”
Section: Attachment-asmentioning
confidence: 99%
“…Insecure or disorganized caregiver attachment in early life has been significantly associated with childhood depression [72] or depressive symptoms in adolescents [73]. A large 17-year cohort study found that childhood maltreatment was associated with a 3-fold increase in depression and/or suicidal risk in adolescence and young adulthood in comparison to those without history of maltreatment, with sexual abuse being the strongest predictor of both phenomena [74].…”
Section: Mddmentioning
confidence: 99%
“…Other research has linked anxious attachment to ERS, a maladaptive behavior characteristic of individuals with depression (Abela, Hankin, Haigh, Adams, Vinokuroff, & Trayhem, 2005;Davila, 2001;Evraire & Dozois, n.d.;Hammen, 1991;Timmons & Joiner, 2008;Shaver, Schachner, & Mikulincer, 2005). ERS is defined as "the relatively stable tendency to excessively and persistently seek assurances from others that one is lovable and worthy, regardless of whether such assurance has already been provided" (Joiner, Matalsky, Katz, & Beach, 1999, p. 270).…”
Section: Anxious Attachment and Self-worthmentioning
confidence: 99%